Plastome sequences fail to resolve shallow level relationships within the rapidly radiated genus Isodon (Lamiaceae) - Chen, Ya-Ping; Zhao, Fei; Paton, Alan J.; Sunojkumar, Purayidathkandy; Gao, Lian-Ming; Xiang, Chun-Lei (Frontiers in Plant Science, 2022)
As one of the largest genera of Lamiaceae and of great medicinal importance, Isodon is also phylogenetically and taxonomically recalcitrant largely ascribed to its recent rapid radiation in the Hengduan Mountains. Previous molecular phylogenetic studies using limited loci have only successfully resolved the backbone topology of the genus, but the interspecific relationships suffered from low resolution, especially within the largest clade (Clade IV) which comprises over 80% species. In this study, we attempted to further elucidate the phylogenetic relationships within Isodon especially Clade IV using plastome sequences with a broad taxon sampling of ca. 80% species of the genus. To reduce systematic errors, twelve different plastome data sets (coding and non-coding regions with ambiguously aligned regions and saturated loci removed or not) were employed to reconstruct phylogeny using maximum likelihood and Bayesian inference. Our results revealed largely congruent topologies of the 12 data sets and recovered major lineages of Isodon consistent with previous studies, but several incongruences are also found among these data sets and among single plastid loci. Most of the shallow nodes within Clade IV were resolved with high support but extremely short branch lengths in plastid trees, and showed tremendous conflicts with the nrDNA tree, morphology and geographic distribution. These incongruences may largely result from stochasticity (due to insufficient phylogenetic signal) and hybridization and plastid capture. Therefore, the uniparental-inherited plastome sequences are insufficient to disentangle relationships within a genus which has undergone recent rapid diversification. Our findings highlight a need for additional data from nuclear genome to resolve the relationships within Clade IV and more focused studies to assess the influences of multiple processes in the evolutionary history of Isodon. Nevertheless, the morphology of the shape and surface sculpture/indumentum of nutlets is of systematic importance that they can distinguish the four major clades of Isodon.